2020
DOI: 10.1155/2020/5618127
|View full text |Cite
|
Sign up to set email alerts
|

The Regenerative Potential of Donkey and Human Milk on the Redox-Sensitive and Proliferative Signaling Pathways of Skin Fibroblasts

Abstract: The influence of milk bioactive peptides on skin regenerative potential and rejuvenation is very often limited because of allergic reactions. The current study is aimed at exploring the influence of donkey colostrum and mature milk, human colostrum and mature milk, and β-casein and β-casomorphine-7, on the growth and inflammatory response of the culture of cultured skin fibroblasts exposed to these conditions for twenty-four hours. Their effects on the growth-regulatory kinases and redox-sensitive, proinflamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…Accordingly, it can be concluded that casein amino acids may be responsible for the activation and proliferation of the cell cycle initiated by Erk. It suggests that noncasein bioactive peptides of donkey and human milk may be responsible for anti-inflammatory properties and may be useful in wound healing, regenerative, and aesthetic dermatology [ 185 ].…”
Section: Milk- and Colostrum-based Products In Cosmetics And Dermatologymentioning
confidence: 99%
“…Accordingly, it can be concluded that casein amino acids may be responsible for the activation and proliferation of the cell cycle initiated by Erk. It suggests that noncasein bioactive peptides of donkey and human milk may be responsible for anti-inflammatory properties and may be useful in wound healing, regenerative, and aesthetic dermatology [ 185 ].…”
Section: Milk- and Colostrum-based Products In Cosmetics And Dermatologymentioning
confidence: 99%
“…The expression level of type 1 collagen was significantly increased with milk exosomes, especially Col M-exo in UV radiation-exposed fibroblasts. According to the previous studies, bovine milk induces type 1 collagen synthesis through the STAT6 pathway in human fibroblast [48] and donkey and human milk activate growth-regulatory kinases, especially the p-ERK pathway, promoting cell cycle and proliferation of skin fibroblasts in vitro [27]. Additionally, we conducted a wound-scratch test to confirm the migration promoting effect of Col M-exo.…”
Section: Skin Elasticity Improvement Effect Of Col M-exo On Fibroblastsmentioning
confidence: 99%
“…Taken together, these findings suggest that Col M-exo can effectively promote ECM construction by improving survival of skin fibroblasts and collagen production under UV irradiation, offering strength and elasticity to the skin. broblasts in vitro [27]. Additionally, we conducted a wound-scratch test to confirm the migration promoting effect of Col M-exo.…”
Section: Skin Elasticity Improvement Effect Of Col M-exo On Fibroblastsmentioning
confidence: 99%
See 1 more Smart Citation
“…75 collagen synthesis through the STAT6 pathway in human fibroblast 91 and donkey and human milk exosomes activate the p-ERK pathway, promoting cell cycle and proliferation of skin fibroblasts in vitro. 92 Human trophoblast exosomes (hTB-Exos) stimulated a decrease in MMP gene expression and an increase in collagen, elastin, and fibronectin gene expression in human normal dermal fibroblasts (HNDFs). The increased expression of genes was associated with C-X-C motif ligand (CXCL) chemokines, toll-like receptors, and nuclear factor-kappa B (NF-κB) signaling.…”
Section: F I G U R Ementioning
confidence: 99%